2020
DOI: 10.29312/remexca.v11i1.2162
|View full text |Cite
|
Sign up to set email alerts
|

Mejorando rasgos biométricos de plántulas de trigo con la inoculación de un consorcio nativo de Bacillus

Abstract: Las bacterias promotoras del crecimiento vegetal (BPCV) representan una alternativa para la disminución del uso de fertilizantes químicos y la mejora del aprovechamiento de estos por los cultivos agrícolas. En el estudio se determinó la capacidad de un consorcio bacteriano nativo del género Bacillus para promover el crecimiento de plántulas de trigo (Triticum turgidum subsp. durum) bajo condiciones controladas, a los 30 días después de su inoculación. El consorcio se integró por las cepas TRQ8, TE3T, TRQ65 y T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…Durum (wheat) under non-stress conditions, reported an increase in plant length and weight, as well as the biovolume index, compared to inoculations of a single bacterial strain at a time. Similarly, Robles Montoya et al [84] reported that the use of a Bacillus consortium composed of B. paralicheniformis, B. subtilis, B. megaterium, and B. cabrialesii with wheat showed a significant increase (compared to un-inoculated seedlings) in the length of the aerial part of the plant, root length, total length, stem diameter, circumference, dry weight of the aerial part of the plant, and the biovolume index.…”
Section: Plant Growth Stimulation By Pgpb Consortia Under Non-stress Conditionsmentioning
confidence: 90%
“…Durum (wheat) under non-stress conditions, reported an increase in plant length and weight, as well as the biovolume index, compared to inoculations of a single bacterial strain at a time. Similarly, Robles Montoya et al [84] reported that the use of a Bacillus consortium composed of B. paralicheniformis, B. subtilis, B. megaterium, and B. cabrialesii with wheat showed a significant increase (compared to un-inoculated seedlings) in the length of the aerial part of the plant, root length, total length, stem diameter, circumference, dry weight of the aerial part of the plant, and the biovolume index.…”
Section: Plant Growth Stimulation By Pgpb Consortia Under Non-stress Conditionsmentioning
confidence: 90%
“…Bacillus megaterium TRQ8, B. cabrialesii TE3 T , and B. paralicheniformis TRQ65 were obtained from the microbial collection named Coleccion de Microorganismos Edáficos y Endófitos Nativos (COLMENA, , accessed on 11 February 2019) [ 8 , 59 ]. These strains were isolated from wheat crop rhizosphere in commercial fields located in the Yaqui Valley (27°00′ and 28°00′ N and 109°30′ and 110°37′ W) and have been previously characterized for their PGP traits (at a genomic, metabolic, and functional level) [ 8 , 11 , 12 , 15 , 16 , 32 , 33 , 34 , 60 ].…”
Section: Methodsmentioning
confidence: 99%
“…Obregon, Sonora, México [43]. Wheat seeds were surface sterilized according to Robles Montoya et al (2020) [44] using 0.1% sodium hypochlorite (30 s), washed twice with sterilized distilled water (30 s), and incubated for five days at room temperature (25 • C) until germination. Subsequently, the seedlings were placed in sterilized and hermetic containers (washed with ethanol at 70% v/v and treatment with ultraviolet light for 1.5 h) with 130 g of an autoclaved substrate (30 min, 121 • C, 15 lbs in three 24 h intervals) (soil (40%): perlite (60%)) [45].…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%